Cellular and molecular mechanisms of antifungal innate immunity at epithelial barriers: The role of C‐type lectin receptors. Issue 3 (6th February 2020) - Borriello, Francesco; Zanoni, Ivan; Granucci, Francesca
Abstract: Humans are constantly exposed to fungi, either in the form of commensals at epithelial barriers or as inhaled spores. Innate immune cells play a pivotal role in maintaining commensal relationships and preventing skin, mucosal, or systemic fungal infections due to the expression of pattern recognition receptors that recognize fungal cell wall components and modulate both their activation status and the ensuing adaptive immune response. Commensal fungi also play a critical role in the modulation of homeostasis and disease susceptibility at epithelial barriers. This review will outline cellular and molecular mechanisms of anti‐fungal innate immunity focusing on C‐type lectin receptors and their relevance in the context of host‐fungi interactions at skin and mucosal surfaces in murine experimental models as well as patients susceptible to fungal infections. Abstract : C‐type lectin receptor (CLR) mediated recognition of fungi by innate immune cells at the epithelial barriers prevents recurrent fungal infections and establishes host‐fungi commensal relationships. These concepts have been demonstrated in mouse models and patients with primary immunodeficiencies affecting the function of CLRs (e.g. dectin‐1) or their signaling molecules (e.g. CARD9).